Plant-based production and characterization of a promising Fc-fusion protein against microgravity-induced bone density loss - Xiong, Yongao; Hirano, Hiroto; Lane, Nancy E.; Nandi, Somen; McDonald, Karen A. (Frontiers in Bioengineering and Biotechnology, 2022)
Microgravity-induced bone loss is a main obstacle for long term space missions as it is difficult to maintain bone mass when loading stimuli is reduced. With a typical bone mineral density loss of 1.5% per month of microgravity exposure, the chances for osteoporosis and fractures may endanger astronauts’ health. Parathyroid Hormone or PTH (1-34) is an FDA approved treatment for osteoporosis, and may reverse microgravity-induced bone loss. However, PTH proteins requires refrigeration, daily subcutaneous injection, and have a short shelf-life, limiting its use in a resource-limited environment, like space. In this study, PTH was produced in an Fc-fusion form via transient expression in plants, to improve the circulatory half-life which reduces dosing frequency and to simplify purification if needed. Plant-based expression is well-suited for space medicine application given its low resource consumption and short expression timeline. The PTH-Fc accumulation profile in plant was established with a peak expression on day 5 post infiltration of 373 ± 59 mg/kg leaf fresh weight. Once the PTH-Fc was purified, the amino acid sequence and the binding affinity to its target, PTH 1 receptor (PTH1R), was determined utilizing biolayer interferometry (BLI). The binding affinity between PTH-Fc and PTH1R was 2.30 x 10-6 M, similar to the affinity between PTH (1–34) and PTH1R (2.31 x 10-6 M). Its function was also confirmed in a cell-based receptor stimulation assay, where PTH-Fc was able to stimulate the PTH1R producing cyclic adenosine monophosphate (cAMP) with an EC50 of (8.54 ± 0.12) x 10-9 M, comparable to the EC50 from the PTH (1-34) of 1.49 x 10-8 M. These results suggest that plant recombinant PTH-Fc exhibits a similar binding affinity and potency in a PTH1R activation assay compared to PTH. exhibits a similar potency compared to PTH. Furthermore, it can be produced rapidly at high levels with minimal resources and reagents, making it ideal for production in low resource environments such as space.